Handbook of alternative materials in residential construction - Bynum, Richard T. (McGraw-Hill, 1999)
This text offers information on alternative construction materials that are proven, more durable and easier to work with than wood, and will save construction time and cost. A case study chapter provides actual plans and CAD drawings from residential buildings that were created from new materials.